(untitled) (Research, Society and Development, 2024)
Pirarucu (Arapaima gigas) is one of the largest freshwater fish in the world. Dried salted fillet of pirarucu is the main product commercialized in northern Brazil, whereas frozen and smoked fillets are less frequently available. The present study aimed to produce canned pirarucu from wild fishing and pisciculture to add value, encourage fish consumption, and diversify canned fish products, as well as to subsequently evaluate the microbiological quality and physicochemical and sensorial characteristics these products. The fillets were sanitized in chlorine solution, immersed in brine (3% refined salt), drained, cut, and packed in cans. Thereafter, 2% hot brine was added, and the cans were subjected to exhaustion, seaming, thermal treatment, and cooling. The containers that revealed no bulging, pinholes, or leaks, and pH<0.2, measured both before and after incubations, indicated that the samples were commercially sterile. The canned fillets presented limited ash content variability, and no significant difference was observed in the moisture, lipid, or protein content. Moreover, sensory tests revealed that the canned fillet prepared with pirarucu from pisciculture was preferred over those prepared with wild-caught fish in terms of texture, flavour, and overall impression attributes, thereby directly reflecting a positive purchase intention for the product. Furthermore, canned pirarucu, whether originating from wild fishing or pisciculture, is a product with high nutritional value and sanitary quality, valuable sensory acceptance, and extended shelf life.